Pengaruh Modul Bergambar Terhadap Peningkatan Keberhasilan Toilet Training Anak Toddler Di Puskesmas Sibela Surakarta - Ros Endah Happy Patriyani; Sunarsih Rahayu (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Pictured module, Toilet Training, Toddler. One of development stage that must achieve in 1 – 3 years old (toddler) is toilet training. In a toddler, the ability of sfingter urethra that was functioned for controlled sensation wants to defecation and sensation want to urinary started development so that its sfingter more ability for controlling sensation want to urinary and sensation want to defecation. Each child had deference of ability and time to reach its ability. One strategy that can was used to parent for help ready to toilet training for a child with a used pictured module. Knowing is the effect of pictured module conduct to increased of resulting toilet training of toddler in work of area of sibela primary health care of Surakarta. The study was using a quasi experiment method with pre-test – post-test design. Analyze data was using the dependent t-test. Pictured module can increase of resulting toilet training of toddler with a value of p=0.002. Occurs increased of resulting toilet training 1.070 points, with correlation level is low (correlation value was 0.683). The nurse must give support for mothers of a toddler, and usually monitored increased of resulting in toilet training for toddler periodically in work of area of Sibela Primary Health Care of Surakarta.